EVALUATION OF THE COHESIVE PROPERTIES OF SBS-MODIFIED BINDERS AT LOW TEMPERATURES - Kok, Baha Vural; Erkus, Yunus; Yilmaz, Mehmet (Sciendo, 2021)
The durability, fatigue resistance, and low-temperature behavior of asphalt layers are greatly affected by the properties of bitumen. Therefore, the composition of bitumen is frequently modified to improve the performance of asphalt mixtures. Styrene-butadiene-styrene (SBS) has been the most often used additive recently. Researchers are trying to improve the cohesive and adhesive properties of binders by such polymer-based additives. In this study, 160/220 penetration grade bitumen and Kraton D 1101 SBS were used. The present study contains a new evaluation for determining the cohesive behavior of SBS-modified binders at -1 degrees C, -3 degrees C, and -5 degrees C. The results of this evaluation were compared to conventional and rheological test results. Penetration, softening point, viscosity, dynamic shear rheometer, and bending beam rheometer tests were therefore conducted. Finally, the results of a low-temperature tensile test were found to be consistent with the results of the other tests; hence, they also confirm the cohesive behavior of SBS-modified binders at low temperatures.
Keywords: Bitumen; Cohesion; SBS; Modification; Low temperature